2013
DOI: 10.1111/codi.12072
|View full text |Cite
|
Sign up to set email alerts
|

The value of inflammation markers and body temperature in acute diverticulitis

Abstract: WBC count and body temperature are of no value in discriminating complicated from uncomplicated diverticulitis. Only CRP can be used as an indicator for the presence of complications, but a low CRP does not mean that complicated disease can safely be excluded. Therefore, radiological examination remains central in the diagnostic work-up of patients presenting with diverticulitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 9 publications
5
62
1
6
Order By: Relevance
“…Studies have shown that certain elevated inflammatory markers may have potential use in differentiating between complicated and uncomplicated cases, yet their exact role is yet to be defined. (14)(15)(16)(17)(18)(19)(20)(21) Table 3 demonstrates recent studies that have been conducted and the findings of significance for the biochemical marker tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that certain elevated inflammatory markers may have potential use in differentiating between complicated and uncomplicated cases, yet their exact role is yet to be defined. (14)(15)(16)(17)(18)(19)(20)(21) Table 3 demonstrates recent studies that have been conducted and the findings of significance for the biochemical marker tested.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have also shown WBC to be higher in complicated diverticulitis (15,17,18) Bilirubin on the other hand is a marker that has had very little investigation in relation to acute diverticulitis although being shown to have high sensitivities and specificities for perforation in acute sigmoid diverticulitis. (18) Hyperbilirubinemia has been described in case reports of complicated acute diverticulitis (26,27)and has been linked to extra-hepatic bacterial infection inducing cholestasis and hepatic portal vein gas as a cause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This modified version includes the substage Ia, which can now be differentiated due to recent technological advances. The degrees of radiological classification, together with clinical data, allow for a better management of this clinical entity (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%